PS2:23 Anti-c1q antibodies in turkish systemic lupus erythematosus patients. (21st March 2018) - Tekeoglu, S; Temiz Karadag, D; Ozdemir Isik, O; Yazici, A; Cefle, A
Abstract : Purpose: Anti-C1q has been shown to be associated with systemic lupus erythematosus (SLE) and disease activity of lupus nephritis in previous studies. We studied anti-C1q specificity for SLE versus rheumatic disease controls and healthy controls and the association with SLE manifestations in a single centre cross-sectional study. Methods: Demographics, disease information and blood samples were obtained during routine follow-up visits of patients attending Kocaeli University rheumatology outpatient clinic. There were 150 SLE patients (92% female, mean: 46 years). Control group had 85 rheumatoid arthritis patients, 16 patients with other diseases (Sjogrens's syndrome, systemic sclerosis, adult onset Still disease, psoriatic arthritis) and 49 healthy persons (88% female, mean: 45 years). Anti-C1q was measured by ELISA according to manufacturer's instructions. Results: In SLE group 72 patients had renal, 10 patients had neurologic disease, 25 patients had antiphospholipid syndrome (APS). Anti-dsDNA was positive in 92 patients, anti-Sm was positive in 18 patients, 83 patients had low complement levels. Prevalence of anti-C1q was 5% (8/150) in patients with SLE and 1% (2/150) in controls (p=0.88). There was no correlation between clinics (renal, neurologic, hematologic, mucocutanous disease, arthritis, serositis, APS) or laboratory findings (Anti-dsDNA, anti-Sm, low complement levels, direct Cooms' test). Within anti-C1q positive group 6 patients had renal disease, 4 had SLEDAI scores 4 or more. None of them had nervous system disease. Six patients had leukopenia, 2 had thrombocytopenia, 5 had mucocutanous disease. Laboratory findings were as follows; 6 patients had anti-dsDNA, 1 had anti-Sm antibody, 6 had low complement levels. Conclusions: Even though there were studies showing the relationship between anti-C1q antibodies and renal disease, it was shown that most of the patients with antibody positivity were Asian ethnicity and younger than 30 years of age. Furthermore anti-C1q antibody was related to disease activation and eliminated within 3 months of treatment. There were also different commercial products available with different cut-off levels. Meta-analysis have shown although anti-C1q antibodies are associated with lupus nephritis, the post-test probabilities are not sufficient to provide certainty of the presence or absence of history of disease.